2021
DOI: 10.7554/elife.65924
|View full text |Cite
|
Sign up to set email alerts
|

A mobile genetic element increases bacterial host fitness by manipulating development

Abstract: Horizontal gene transfer is a major force in bacterial evolution. Mobile genetic elements are responsible for much of horizontal gene transfer and also carry beneficial cargo genes. Uncovering strategies used by mobile genetic elements to benefit host cells is crucial for understanding their stability and spread in populations. We describe a benefit that ICEBs1, an integrative and conjugative element of Bacillus subtilis, provides to its host cells. Activation of ICEBs1 conferred a frequency-dependent selectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 72 publications
2
37
0
1
Order By: Relevance
“…We previously demonstrated that B. subtilis biofilm formation promotes the transfer of ICE Bs1 and that the production of the biofilm matrix exopolysaccharide (EPS) and amyloid-like fibers (TasA) is required for this high efficiency (33). This observation was corroborated by others who also showed that ICE Bs1 encodes for a protein, DevI, able to influence biofilm formation (34). Here, we took advantage of the high propagation of ICE Bs1 in B. subtilis biofilms to better understand the spatiotemporal parameters of conjugation in biofilms using fluorescent microscopy.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…We previously demonstrated that B. subtilis biofilm formation promotes the transfer of ICE Bs1 and that the production of the biofilm matrix exopolysaccharide (EPS) and amyloid-like fibers (TasA) is required for this high efficiency (33). This observation was corroborated by others who also showed that ICE Bs1 encodes for a protein, DevI, able to influence biofilm formation (34). Here, we took advantage of the high propagation of ICE Bs1 in B. subtilis biofilms to better understand the spatiotemporal parameters of conjugation in biofilms using fluorescent microscopy.…”
Section: Introductionsupporting
confidence: 72%
“…However, we did not observe a significant difference in the proportion of transconjugants cells expressing P tapA - yfp in comparison to the proportion observed for all recipient cells (Figure 1C). This discrepancy might be due to the fact that biofilm formation can be inhibited in transconjugants following the acquisition of ICE Bs1 via expression of DevI, as previously reported by Jones et al ., thus limiting the expression of the fluorescent reporter in transconjugant cells (34).…”
Section: Resultsmentioning
confidence: 99%
“…Ectopic expression alleles controlled by P xis were designed at lacA , as previously described (Jones et al, 2021), to test the sufficiency of Tn 916 genes to cause growth defects. Briefly, orf16 , orf17 , or orf17 - 16 together were fused with P xis , an MLS resistance cassette, and up- and downstream homology arms via isothermal assembly and transformed into B. subtilis , selecting for acquisition of MLS resistance.…”
Section: Methodsmentioning
confidence: 99%
“…Conjugative elements can also have more complex relationships with their host cells. Some elements encode functions that manipulate host development, growth, and viability (for examples see (Beaber et al, 2004;Jones et al, 2021;Pembroke and Stevens, 1983;Reinhard et al, 2013)). Excessive mating events can be detrimental to host viability (Avello et al, 2019;Skurray and Reeves, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Prokaryote genomes typically contain a variety of mobile genetic elements (MGEs), such as plasmids 1 , phages, transposons or integrative and conjugative elements (ICEs) 2,3 , which largely contribute to host evolution and community-wide adaptation through genome rearrangements and horizontal gene transfer [4][5][6] . Although transfer mechanisms per se are well understood, it is insufficiently appreciated that MGEs form their own entities embedded within the host, undergoing selection towards their own fitness optimization [7][8][9][10][11] ; for example, by increasing transfer success to new cells 12,13 . MGE decisions potentially oppose the interests of the host cell 14,15 and can inflict serious damage by cell lysis 16,17 or cell division inhibition [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%